Experimental Behavior of High Strength Concrete Filled Double Skin Steel Tubular Columns - Mahdi Saleh, Samoel; Hameed Majeed, Fareed (Iraqi Journal of Civil Engineering, 2018)
A series of experimental tests were carried out to investigate the behavior of high strength concrete filled double skin steel tubular (HSCFDST) columns. Fourteen column specimens were tested in the present study, taking into account the effects of the shape of column cross section (circular or square), the hollowness ratio, and the slenderness ratio. For comparison, two of the tested specimens were filled with normal strength concrete. It was seen that the ultimate axial strength of the square HSCFDST columns is greater than that for circular ones, in spite of that the sectional properties were approximately equal. Also, it was found that for both circular and square column specimens, the ultimate axial strength of HSCFDST columns was inversely proportional to their hollowness and slenderness ratios. CFDST column specimens filled with high strength concrete compared with those filled with normal strength concrete increased stiffness and ultimate axial strength, but give unexpected results for the ultimate axial strength, therefore the suitable choice for the section properties of the inner steel tube is required. The experimental results and analytical approach that developed by other researchers shown good agreement.